The Role of Village Government in Efforts to Improve the Welfare of Fishermen's Communities In Corawali Village, Tanete Rilau District Barru Regency - St. Aisyah; Maldives; Aisha R. Manou (Yayasan Amerta Insan Unggul, 2024)
This study aims to analyze the role of the village government in improving the welfare of fishing communities in Corawali Village, Tanete Rilau District, Barru Regency. A qualitative descriptive method was employed to provide an in-depth understanding of the government’s contribution to local fishermen’s economic and social well-being. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the economic conditions of fishermen in Corawali Village remain modest, with most relying on traditional fishing methods and limited access to capital and technology. The village government, in collaboration with the Barru Regency Fisheries and Marine Office, has implemented several empowerment initiatives, such as training programs, capital assistance, and boat repair support. Although these efforts have positively influenced fishermen’s income and self-reliance, the outcomes have not been optimal due to challenges like fluctuating weather, low education levels, and inadequate infrastructure. The study concludes that strengthening village government capacity, improving transparency in program implementation, and fostering partnerships with external institutions are crucial to achieving sustainable welfare among fishing communities.